Exploring Gender-Specific Correlations Between Nutritional Intake, Body Composition, Psychological Skills, and Performance Metrics in Young Taekwondo Athletes - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Objectives: Taekwondo performance is influenced by a complex and dynamic interplay of physical, nutritional, and psychological factors, all of which contribute to competitive success. However, the gender-specific relationships among these factors in young high-performance athletes remain understudied. This study aimed to fill in this knowledge gap. Methods: A cross-sectional study was conducted with 35 elite taekwondo athletes (male: n = 20, female: n = 15, age: 13 ± 1 years). Participants underwent anthropometric assessments, dietary evaluations, and psychological skill assessments during an 8-week training camp before the World Taekwondo Championships. Physical performance was assessed using the Frequency Speed of Kick Test (FSKTmult) and the Taekwondo-Specific Agility Test (TSAT). Statistical analyses included independent t-tests, correlation analyses, and regression models. Results: Males exhibited significantly higher fat-free mass (FFM: 42.8 ± 2.9 kg vs. 36.3 ± 1.6 kg, p < 0.001), skeletal muscle mass (SMM: 31.1 ± 2.2 kg vs. 28.2 ± 1.6 kg, p < 0.001), and energy intake (32.4 ± 4.6 kcal/kg vs. 29.3 ± 3.1 kcal/kg, p = 0.032) than females. Males also had greater dietary intakes of vitamin A, vitamin C, magnesium, and iron (all p < 0.05). There were no gender differences in any psychological attributes associated with emotional intelligence, sport success perception, and mental toughness. Although the total kick count in the FSKTmult was similar for male and female taekwondo athletes (100.2 ± 4.6 vs. 97.5 ± 5.9 kicks, p = 0.139), males outperformed females in round 4 (19.4 ± 1.1 vs. 18.6 ± 1.4 kicks, p = 0.048) and round 5 (18.2 ± 1.0 vs. 17.2 ± 1.0 kicks, p = 0.007) of this test, suggesting higher physical performance maintenance during the test. Regression models indicated that body mass (β = 0.901, p < 0.001) and calcium intake (β = 0.284, p = 0.011) predicted performance in males, while body mass (β = 1.372, p < 0.001), protein intake (β = 0.171, p = 0.012), and emotional regulation (β = 0.174, p = 0.012) were key predictors in females. Conclusions: These findings highlight the importance of an integrated approach to training, nutrition, and psychological preparation in optimizing taekwondo performance. While males and females demonstrated similar psychological resilience and total kick output in a taekwondo-specific test, males exhibited superior endurance in later test rounds of this test. Performance optimization in young elite taekwondo athletes may require the implementation of gender-specific training and nutrition strategies, emphasizing body weight control and calcium intake for males and protein intake for females. © 2025 by the authors.